KONSTRUKSI GAYA RETORIKA FREDRICH YUNADI (Analisis Retorika Aristoteles Program Televisi Catatan Najwa Edisi “Setia Pengacara Setya”) - Edward Natanael; Cosmas Gatot Haryono (Universitas Bunda Mulia, 2018)
ABSTRACTThis study seeks to see the rhetoric used by Fredrich Yunadi in the interview “Catatan NajwaSetia pengacara Setya” in case of corruption in the procurement of ID cards. In that program, thedefense of Fredrich as Setya Novanto's lawyer who seemed excessive, just became a unique andinteresting thing to study. This study uses qualitative research methods and descriptive approaches usingthe theory of rhetoric and construction of media reality. The results of this study are the loyalty ofFredrich Yunadi in the interview program. Note Najwa's edition of